AGRICULTURAL INFORMATION SYSTEM OF SWEET CORN IN LABANAN VILLAGE - Syafei Karim; Adelia Adelia Juli Kardika; Andi Lisnawati; Husmul Beze; Reza Andrea; Eva Nurmarini; Wardatul Hidayah; Diepa Febriana Wulandari, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Monitoring of sweet corn farming in Labanan village is still done conventionally, where landowners must go to the land to do fertilization, weed removal, and harvesting, as well as delivery of crops to collectors. The condition of the land from one land to another which is quite far apart and the non-uniformity of planting corn makes it difficult for land owners to monitor. To use to overcome this problem, it is necessary to create an information system that can help land owners manage land sweet corn farm. System development begins with identifying problems for know the flow of the system, design using Entity Relationship Diagram (ERD) and Data Flow Diagram (DFD), then continued with the implementation of the system using the PHP programming language with MySQL database. The information system that has been successfully built can be accessed by 4 users, namely admins, land owners, farmers, and collectors. This system can help manage user data, farmer data, land owner data, collector data, supply demand data, land data, and land detail data. The information system that has been successfully built is then carried out functional testing using black box. The test results show that all functions on the system have been running well